Rule of phases and variance of phase processes in systems with fixed components. - A. K. Frolkova; G. I. Tatsievskaya; L. A. Khakhin (Тонкие химические технологии)
The rule of phases for systems with fixed components and variance of phase processes in such systems, including variance of one-stage phase processes and process of extractive rectification taking into account intensive, extensive and constructive variables is considered